PERSEPSI DAN PARTISIPASI NELAYAN DALAM PEMANFAATAN TEMPAT PANGKALAN PENDARATAN IKAN (PPI) KELURAHAN SELILI DI KOTA SAMARINDA - Zainal Abidin; Haqiqiansyah, Gusti; Darmansyah, Oon (Jurnal Pembangunan Perikanan dan Agribisnis, 2024)
The study aims to determine the level of perception and participation of fishermen in the utilization of the Selili Fish Landing Base in Samarinda City. The sampling technique used is Incidental sampling method. The results of this study indicate that the perception level of fishermen in the utilization of the Fish Landing Base is 31.69, which is in the interval of 28.01 - 36.00 so that it is included in the high category. The participation rate of fishermen in the utilization of the Landing Base is 76%, this value is in the high category, meaning that the participation of fishermen has helped in the utilization of the Selili Landing Base